ORIENTING POINTSOF MODERN POLYCULTURAL EDUCATION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with the orienting points of multicultural education in the modern educational space. Emphasis is placed on the social upbringing of an individual in the context of cultural dialogue; education of tolerance and taking into account the reli- gious and ethnic culture of the individual; mastering the universal values of world and national culture; fostering a culture of international communication. The author focuses on the main features of multicultural education as an important way of forming certain social-educational and value-oriented inclinations, communicative and empathic skills that allow a person to carry out intercultural interaction, and to show understanding of other cultures, tolerance towards them.On the basis of the conducted research the author's vision of the essence of multicultural education of the modern personali- ty is formed, in particular purposeful socialization of the personality, which necessarily includes assimilation of samples and values of world culture, cultural-historical and social experience of different countries and peoples; formation of social-attitudinal and value-oriented qualities of a person capable of effective intercultural communication, as well as development of tolerance towards other countries, peoples, cultures and social groups; active social interaction. with representatives of different cultures while maintaining their own cultural identity.The goals, principles, functions of multicultural education in the theory and practice of educational process are considered.
Keywords: multicultural education, tolerance, multicultural environment, dialogue of cultures, orienting points, approaches, principles, functions.